Effects of Diacetoxyscirpenol and Fusaric Acid on Poults: Individual and Combined Effects of Dietary Diacetoxyscirpenol and Fusaric Acid on Turkey Poult Performance - Fairchild, A.S.; Grimes, J.L.; Porter, J.K.; Jr., W.J. Croom; Daniel, L.R.; Jr., W.M. Hagler (International Journal of Poultry Science, 2005)
Turkey poults were randomly placed in batteries and fed one of four dietary treatments: control (C); control plus 4ppm diacetoxyscirpenol (DAS); control plus 300 ppm (FA); and control plus 4ppm DAS and 300ppm FA (FD). There were 10 poults per pen with 6 replicate pens per treatment. Individual BW, BW gains (BWG) and feed consumption by pen was determined at d6, d12, and d18. Period and cumulative feed to gain was calculated. Mouth lesions were scored for treatments at d18. On d18 poults were euthanized for determination of organ weights and jejunal histomorphometrics. FA had no effect on BW or BWG at any period compared to C. Poults fed FD had reduced BW and BWG compared to C, while poults fed DAS had lower BW than all treatments at every period. Poults fed FA or C had better feed to gain (P